Harnessing the technological potential of chia seeds in the technology of cream-whipped candy masses - Shydakova-Kameniuka, Olena; Shkliaiev, Oleksii; Samokhvalova, Olga; Artamonova, Maya; Stepankova, Galyna; Bolkhovitina, Olena; Rogova, Alla (Eastern-European Journal of Enterprise Technologies, 2020)
The technological properties of chia seeds have been studied. It has been established that the degree of their swelling depends on the type of a medium (water, albumin solution, fat) and the state of seeds (whole seeds or ground seeds). It was noted that the whole seeds have a higher capacity to retain water than the ability to retain an albumin solution or fat, by 1.87 and 17.28 times, and the ground seeds – by 1.75 and 17.49 times, respectively. Their capacity to swell improves after grinding regardless of the type of a medium. In addition, the ground seeds have a better fat-emulsifying ability but they do not demonstrate the foaming properties. The whole chia seeds have good foaming properties. It is possible to obtain a whipped protein mass, which is not worse than the control sample in terms of stability and foaming capacity, in case of replacing 40 % of dry albumin with whole chia seeds. We recommend adding the whole chia seeds at the stage of the whipping of protein mass, and the ground seeds – at the stage of obtaining a fat emulsion semi-finished product in the production of cream-whipped candy masses. Thus, the formulation amount of dry albumin and fat decreases. The addition of 30 % of whole seeds and 30 % of ground seeds helps reduce the density of structured cream-whipped candy mass by 6.7 %. A further increase in the dosage of the additive leads to a slight increase in the value of the density indicator. In addition, an increase in the content of chia seeds causes an increase in the strength indicator of samples. The organoleptic analysis showed that the structured cream-whipped candy masses with the most studied dosage of chia seeds have the densified structure, uneven porosity, and strong, viscous consistency. It was found that the dosage of whole seeds should equal 40 % by weight of egg albumin, and the dosage of ground seeds – 40 % by weight of fat to ensure the high quality of cream-whipped candy masses. The obtained results are of practical importance for improving the technology of cream-whipped candy masses towards decreasing the formulation amount of albumin and margarine. The addition of chia seeds would improve the nutritional and biological values of cream-whipped candies